Artificial : Figuracions contemporànies. - Bonami, Francesco; Grandas, Teresa; Lebrero Stals, José; Molins i Nubiola, Miquel; Peiró, Rosario (Barcelona : MACBA (Museu d'Art Contemporani de Barcelona), 1998)
Artschwager, Richard ; Baldessari, John ; Burki, Marie José ; Cattelan, Maurizio ; Colomer, Jordi ; Demand, Thomas ; Fritsch, Katharina ; Gonzalez-Torres, Felix ; Hablützel, Stefan ; Hanson, Duane ; Hirst, Damien ; Lavier, Bertrand ; Lewis, Mark ; McCollum, Allan ; Morley, Malcolm ; Pascali, Pino ; Ray, Charles ; Richter, Gerhard ; Ruff, Thomas ; Slominski, Andreas
Catalaans
Engels
Spaans
boek